Micro-irrigation for climate-smart agriculture: environmental footprints, greenhouse gas mitigation, and policy pathways - Anchal Dass; Keerthana Maveril; Susama Sudhishri; Pavan P. Panzade (Annals of Agricultural Research, 2025)
Micro-irrigation, such as drip and sprinkler, is at the cutting edge of modern water resource development, with the current challenges of climate change, the shortage of water resources, and the increasing greenhouse gas emissions from agriculture sector. This comprehensive literature review synthesizes data on the efficacy of precision drip micro-irrigation in reducing CO2 emissions due to energy consumption with respect to flood and sprinkler irrigations, indicating a significant reduction in N2O emissions due to optimal soil moisture maintenance, thereby reducing denitrification. In flood-dominated rice ecosystems prevalent in large parts of India; subsurface drip irrigation can significantly lower methane emissions by encouraging a rhizosphere rich in oxygen, in turn, favouring methanotrophic bacteria. In the Indo-Gangetic Plains (IGP), with rice-wheat cropping in Punjab and Haryana having exploited deep groundwater aquifers to their extent, estimates of CO2-equivalent emissions per hectare annually are substantial. With sustained increases in crop productivity gains and with economically advantageous benefit-cost ratio (BCR) values because of subsidies in Pradhan Mantri Krishi Sinchayee Yojana, this initiative is important to harness what is achievable through this system from a technical potential perspective. Life cycle energy studies show that drip irrigation uses much less total energy than sprinkler systems. Scaling-up pathways of PM-KUSUM solar pumping, Digital Agriculture Mission IoT platforms, can lead to a faster and wider diffusion of drip irrigation. A large scale adoption of micro-irrigation can make agriculture environmentally safe, productive and sustainable.